Energy Efficiency of Kenaf Cultivation in Kelantan, Malaysia by Using Data Envelopment Analysis - Alpandi, Rabiatul Munirah; Yaacob, Fatin Farazh; Abdullah, Siti Mariam Melissa; Yusof, Siti Hawa; Mohd Salam, Muhammad Syafiq (Information Management and Business Review, 2023)
Agricultural production has become aggressive energy concentrated in a determination to supply more food to the increasing population and provide sufficient and adequate essentials. The limited natural resources and the effect of the use of different energy sources on the environment and human health such as global warming, it is necessary to investigate energy consumption patterns in agriculture. In this study data envelopment analysis method approach has been used to determine the efficiencies of kenaf farmers concerning energy use in kenaf cultivation production activities in Kelantan, Malaysia. The study’s empirical result will help to segregate the 15 most efficient farmers and inefficient ones. Other than that, the data envelopment analysis method also will help to identify wasteful uses of energy from different sources by inefficient farmers and to suggest reasonable savings in energy uses from different sources of inputs. The rank method and distribution of virtual inputs are used to get insights into the individual Kenaf farmer performance, rank efficient farmers and identify the improved operating practices followed by a group of truly efficient Kenaf farmers. The result of the analysis indicates the average value of technical efficiency, Pure technical efficiency and Scale efficiency scores of kenaf cultivation production were 0.854, 0.962 and 0.887 respectively. These results imply that all inefficient farmers operate at optimum scale size and 11.3% energy saving is possible without affecting Kenaf yield level. Result also reveals higher potential contribution to total energy saving is from fertilizer (86.5%), Diesel (13%), Pesticides (0.3%) and human labor (0.2%).